2021
DOI: 10.1172/jci136055
|View full text |Cite
|
Sign up to set email alerts
|

Circulating markers of NADH-reductive stress correlate with mitochondrial disease severity

Abstract: Conflict of interest:VKM is on the scientific advisory board and receives equity from Janssen Pharmaceuticals and 5AM Ventures. VKM is an inventor on a patent application filed by Massachusetts General Hospital on novel therapeutic approaches targeting reductive stress ("Extracellular Redox Enzyme System to Alleviate Disease," no. 16/769,319). OSS is a paid consultant for Proteinaceous Inc. MH is a paid consultant for Zogenix and Entrada Therapeutics. DCDV is a paid consultant for Biogen and AveXis Therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 92 publications
(126 reference statements)
10
117
0
Order By: Relevance
“…It is interesting that there is very little evidence about the function or role of the N-lactoyl-amino acids, but one study identified the process of their synthesis from lactate and amino acids by protease cytosolic nonspecific dipeptidase 2 by reverse proteolysis and hypothesized that this group of metabolites may represent a large portion of the unidentified metabolites that are regulated by exercise or other stimuli [ 36 ]. Recently, several N-lactoyl-amino acids have been linked to mitochondrial function [ 37 ], which is a crucial aspect of the thermogenic process efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that there is very little evidence about the function or role of the N-lactoyl-amino acids, but one study identified the process of their synthesis from lactate and amino acids by protease cytosolic nonspecific dipeptidase 2 by reverse proteolysis and hypothesized that this group of metabolites may represent a large portion of the unidentified metabolites that are regulated by exercise or other stimuli [ 36 ]. Recently, several N-lactoyl-amino acids have been linked to mitochondrial function [ 37 ], which is a crucial aspect of the thermogenic process efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend using blood instead of urine ketone measurements, both for ease of use and for improved accuracy in the setting of potential secondary mitochondrial deficits in ketone oxidation, where urinary acetoacetate may underestimate the degree of ketosis relative to blood beta-hydroxybutyrate. 83 …”
Section: Specific Care Aspectsmentioning
confidence: 99%
“…The degree of heteroplasmy may explain this finding, as LHON lymphoblasts have a more severe mitochondrial defect (Complex-I), compared to POAG. A certain amount of defective Complex-I must be present before oxidative dysfunction occurs and clinical signs become apparent; this is known as the threshold effect [176]. The threshold for disease is lower in cells/tissues that are highly dependent on oxidative metabolism, such as RGCs versus tissues that are not, such as lymphocytes/lymphoblasts.…”
Section: Increased Nadhmentioning
confidence: 99%